Clinical features of patients with allergic rhinitis and evaluation of adenoid hypertrophy as a comorbidity - Özlem Sancaklı; Halil Belverenli (Galenos Publishing House, 2019)
INTRODUCTION: The nasal cavity is anatomically and functionally associated with eyes, paranasal sinuses, nasopharynx, middle ear and lower airways. Therefore, comorbid diseases such as asthma, chronic sinusitis, adenoid hypertrophy allergic conjunctivitis are common in patients with allergic rhinitis. In our study, we aimed to evaluate the frequency of comorbid diseases, clinical features of patients. METHODS: The study included children aged between 3-17 years who were diagnosed with moderate to severe allergic rhinitis between September 2015 and March 2016 in our pediatric allergy outpatient clinic.Patient files were retrospectively reviewed; comorbid diseases, family history, eosinophil percentage, total IgE level and allergy test results and the number of drugs used were recorded. In the first month of the treatment, visual analog scale was used to score the symptoms.P <0.05 was considered significant in the statistical analysis. RESULTS: A total of 106 patients (33 female, 73 male) with a median age of 7.25 (5.13) [3.0 - 17.0] were included in the study. In 84.9% of our patients, skin test was positive, and in 69.8% of the patients the symptoms persisted for more than 2 years. The most common comorbid diseases were asthma (52.8%) and adenoid hypertrophy (30.2%). In our study, the incidence of adenoid hypertrophy was higher and total IgE levels were lower in the skin test negative group (p = 0.019, p = 0.027). DISCUSSION AND CONCLUSION: In our study, the most common comorbid diseases in patients with allergic rhinitis were asthma and adenoid hypertrophy, and in the skin test negative group adenoid hypertrophy was more frequent.